DO PENSIONS REDUCE THE INCENTIVE TO WORK? EVIDENCE FROM EGYPT - Viet Cuong, Nguyen; Arouri, Mohamed (Economic Annals, 2018)
In this study we investigate the impact of the receipt of contributory and social pensions on the labour supply of individuals in Egypt, using individual fixed-effect regressions and panel data from the Egypt Labour Market Panel Surveys in 2006 and 2012. The study compares the effect of social pensions and contributory pensions. We find that the receipt of contributory pensions reduces the probability of working as well as the probability of having a waged job of household members aged from 15. The receipt of social pensions has no significant effect on the probability of working for those aged 15–60. However, receiving social pensions can reduce both working and labour market participation of people aged over 60.